Multiletramentos e ensino de língua portuguesa: uma proposta de trabalho com gêneros multissemióticos - Piovesan, Ana Valéria (2024)
This study focuses on teaching practices in Portuguese language classes from the perspective of multiliteracies and discursive semiotics. Its general objective is to improve the discursive skills of students in a 2nd year high school class through a didactic sequence focusing on multiliteracies. The theoretical bases are anchored in the theory of Multiliteracies, especially in the premises of Roxane Rojo (2012, 2015), Magda Soares (2016), Mary Kalantzis and Bill Cope (2012) and Angela Kleiman (1995), as well as in precepts of discursive semiotics, based on Algirdas Julius Greimas (2008 and 2014), Diana Luz Pessoa de Barros (2005) and José Luiz Fiorin (2021). As for the methodology, it is an action research that is organized into two parts. It presents, at the beginning, the bibliographical and documentary research, in which the theoretical-methodological concepts that underpin the theory of multiliteracies, discursive semiotics and the National Common Curricular Base (BNCC) were developed. The second part consists of the intervention itself in the classroom, with the application of a didactic sequence to a 2nd year high school class. The activities in the sequence have multisemiotic genres as corpora and the duration is approximately two months. During this period, in addition to the activities proposed to the students, two questionnaires as research instruments - one for survey and one for evaluation - were applied to verify their perceptions regarding the proposal, and a logbook, for notes and records of the observations collected during the throughout classes. In this way, the report of the classes developed and applied follows the analysis of the data from the questionnaire and the logbook. The didactic sequence developed includes the skills required in the guiding document: reading and understanding, speaking, textual production and linguistic/semiotic analysis, promoting the understanding of different textual manifestations. The main results of the research include the development of textual analysis and understanding skills in order to improve writing and oral production of different genres, in addition to improving technological skills and promoting reflection on cultural diversity and respect for differences.